The treatment of endometrial hyperplasia – when surgical treatment is unnecessary - Sobczuk, Anna (Menopause Review/Przegląd Menopauzalny, 2011)
Cooperation between gynecologist and pathologist is essential for both proper diagnosis and treatment. Inappropriate diagnosis of endometrial hyperplasia guides wrong clinical therapy, which can be very different depending on the type of hyperplasia found. Until 1994 the classification of endometrial lesions had been in chaos. The World Health Organization (WHO) 1994 classification is based on the seminal work of Kurman, Kaminski and Norris (1985) ordered the terminology, according to degree of architectural complexity and crowding of endometrial glands and the presence or absence of cytological atypia resulting in a classification system of simple or complex hyperplasia, with/or without atypia. In the same time Mutter and the International Endometrial Collaborative Group has proposed a new term, “endometrial intraepithelial neoplasia” (EIN), to characterize early malignant lesions and classified endometrial lesions in 2 group: benign Endometrial Hyperplasia (EH), Endometrial Intraepithelial Neoplasia (EIN). The new classification is based on integrated morphological, genetic molecular, cell biological and prognostic morphometrical studies and seems to be satisfying in practical medicine due to it is simple, reproducible, and may contribute to a better predict regression and progression to adenocarcinoma and correlation between surgical pathology and clinical management. Treatment guidelines recommend that women with complex hyperplasia can be treated with progestins and women with atypical hyperplasia should be treated with hysterectomy. Treatment regimens should be individualised and hysterectomy with bilateral oophorectomy considered a somewhat aggressive form of management.